Implementasi Kepemimpinan Islam Dalam Proses Inovasi Produk Pada Sentra Batik Jetis Sidoarjo - Ferryanto, Hanif; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine how the implementation of the principles of the Islamic leadership in product innovation process in the Sentra Batik Jetis Sidoarjo.This study used a qualitative approach with descriptive case study method. Data was collected through interviews with business leaders in Sentra Batik Jetis Sidoarjo. Triangulation technique was also carried out in this study to test the credibility of the data. Triangulation technique used in this research is triangulation sources by conducting interviews to workers of batik business leaders, and also triangulation techniques to make observations, anddocumentary evidence in the field.The results obtained from this study indicate that the principle of Islamic leadership has been well implemented by the batik industry leader in Sentra Batik Jetis Sidoarjo. The process of product innovation in the Sentra Batik Jetis Sidoarjo can be done well because it is supported by leaders who have applied the principles of the Islamic leadership is the principle of tawhid, the principle consultation, the principle of freedom of thought and principle of fair.